THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE SATISFACTION AND COMMITMENT - Aprillina, Vina Nur; Rizky, Yorda Bilasang; Rievan, Moch Aldy; Alwi, Muhamad (Ridwan Institute, 2024)
The aim of this research is to examine how leadership style affects worker commitment and satisfaction in the workplace. The study was carried out by literature reviews and surveys with questionnaires. Regression tests are then used to assess the acquired data with the aid of the SPSS software. The study's findings indicate that, at least in part, a leader's style significantly improves employee work satisfaction. Leaders that successfully apply the appropriate leadership style are able to inspire and encourage their workforce. Furthermore, the study demonstrates that workers who believe they are being led by capable executives typically exhibit greater levels of loyalty to the organization.